Nigral and striatal connectivity alterations in asymptomatic LRRK2 mutation carriers: A magnetic resonance imaging study. Issue 12 (21st September 2016) - Vilas, Dolores; Segura, Bàrbara; Baggio, Hugo C.; Pont‐Sunyer, Claustre; Compta, Yaroslau; Valldeoriola, Francesc; José Martí, María; Quintana, María; Bayés, Angels; Hernández‐Vara, Jorge; Calopa, Matilde; Aguilar, Miquel; et al.
ABSTRACT: Background: The study of functional connectivity by means of magnetic resonance imaging (MRI) in asymptomatic LRRK2 mutation carriers could contribute to the characterization of the prediagnostic phase of LRRK2 ‐associated Parkinson's disease (PD). The objective of this study was to characterize MRI functional patterns during the resting state in asymptomatic LRRK2 mutation carriers. Methods: We acquired structural and functional MRI data of 18 asymptomatic LRRK2 mutation carriers and 18 asymptomatic LRRK2 mutation noncarriers, all first‐degree relatives of LRRK2 ‐PD patients. Starting from resting‐state data, we analyzed the functional connectivity of the striatocortical and the nigrocortical circuitry. Structural brain data were analyzed by voxel‐based morphometry, cortical thickness, and volumetric measures. Results: Asymptomatic LRRK2 mutation carriers had functional connectivity reductions between the caudal motor part of the left striatum and the ipsilateral precuneus and superior parietal lobe. Connectivity in these regions correlated with subcortical gray‐matter volumes in mutation carriers. Asymptomatic carriers also showed increased connectivity between the right substantia nigra and bilateral occipital cortical regions (occipital pole and cuneus bilaterally and right lateral occipital cortex). No intergroup differences in structural MRI measures were found. In LRRK2 mutation carriers, age and functional connectivity correlated negatively with striatal volumes. Additional analyses including only subjects with the G2019S mutation revealed similar findings. Conclusions: Asymptomatic LRRK2 mutation carriers showed functional connectivity changes in striatocortical and nigrocortical circuits compared with noncarriers. These findings support the concept that altered brain connectivity precedes the onset of classical motor features in a genetic form of PD. © 2016 International Parkinson and Movement Disorder Society